2022
DOI: 10.1021/acs.langmuir.2c00817
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Mechanical Model Analysis and Visualization Investigation of SiO2 Nanoparticle/HPAM Polymer Foam Liquid Film Displacing Heavy Oil

Abstract: In this paper, the microscopic mechanisms and macroscopic characteristics of polymer/nanoparticle foam flooding in a heavy oil reservoir environment were studied. Sodium dodecyl sulfate (SDS) surfactant was used as the foaming agent, and the foam was prepared by a combination of partially hydrolyzed polyacrylamide (HPAM) polymer and SiO2 nanoparticles. By performing experiments with the microscopic model, the foam flooding dynamics in the heavy oil reservoir were simulated. Based on the experiments, the formul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…As shown in Figure , the research results show that at the same temperature, the dissolved gas–oil ratio of multicomponent gases gradually increases with the increase of pressure, and the increase is nearly linear. However, under the same pressure, the dissolved gas–oil ratio gradually decreases with the increase of temperature because the molecular motion of multicomponent gases is intensified under high-temperature conditions, which is not conducive to its dissolution in heavy oil.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure , the research results show that at the same temperature, the dissolved gas–oil ratio of multicomponent gases gradually increases with the increase of pressure, and the increase is nearly linear. However, under the same pressure, the dissolved gas–oil ratio gradually decreases with the increase of temperature because the molecular motion of multicomponent gases is intensified under high-temperature conditions, which is not conducive to its dissolution in heavy oil.…”
Section: Resultsmentioning
confidence: 99%
“…As a water flooding additive, the HPAM polymer has been widely reported in laboratory research and field application in conventional oil recovery. In addition, studies have shown that the combination of polymer flooding technology and horizontal wells in heavy oil reservoirs has potential applicability. Gu et al used a sodium dodecyl sulfate (SDS) surfactant as a foaming agent to prepare foam by combining the HPAM polymer with SiO 2 nanoparticles. Through a microscopic model experiment, the foam driving mechanics of a heavy oil reservoir are simulated.…”
Section: Introductionmentioning
confidence: 99%
“…To tackle the challenges associated with surfactant flooding, the utilization of nanoparticles has recently been proposed due to their distinctive properties. , Nanoparticles, characterized by their nanometer-scale size (1–100 nm) and large surface area, possess unique physical and chemical attributes that make them well-suited for the application in chemical EOR. Recently, researchers have conducted extensive experimental investigations to assess the performance of various nanoparticles in the field of EOR. For instance, Olayiwola and Dejam conducted experimental analyses to examine the mechanism of injecting nanoparticles, low salinity water (LSW), and surfactants into sandstone reservoirs to enhance oil recovery.…”
Section: Introductionmentioning
confidence: 99%